(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper will examine effects of migration on rural youths of Uttarakhand. The survey, study of migration commission report 2018on rural youths will tell the actual situation, a short review on the situation of youths. The economy is called “Money order economy” so the present economy review will also be including. The youths always play important role in every state. There are always many hindrances facing by rural youths i.e. poverty, unemployment, education etc. The state government is trying to improve situation of youths and there are some survey, data based on them.